Nine gems of sanskrit literature - Menon, K. P. A. (New Delhi, 1996)
This book is emphasized on Sanskrit literature. It is followed by the Kalavadhakavyam and Durgastuti of the famous saint poet.
Keywords: Sanskrit literature-Translation into english